MULTIPROFESSIONAL CARE FOR THE LGBT PUBLIC - Monique Alves Desidério, Bárbara; Candido Santos Junior, Carlos; Corrêa Bezerra de Araújo, Renata; da Silva Carvalho, Denise; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
The National Policy for Comprehensive LGBT Health in SUS practices aims to promote the comprehensive health of the LGBT population (Lesbians, Gays, Bisexuals, Transvestites and Transsexuals). There is an understanding of society’s constant updating on the respective subject and thus generating other segments of life that must be updated in order to accompany this process. One aspect aimed at this update is the nursing consultation on sexuality for and with this public, respecting differences and addressing myths, ancient knowledge, prejudices and taboos.